Complete revascularisation versus treatment of the culprit lesion only in patients with ST-segment elevation myocardial infarction and multivessel disease (DANAMI-3—PRIMULTI): an open-label, randomised controlled trial. Issue 9994 (15th August 2015) - Engstrøm, Thomas; Kelbæk, Henning; Helqvist, Steffen; Høfsten, Dan Eik; Kløvgaard, Lene; Holmvang, Lene; Jørgensen, Erik; Pedersen, Frants; Saunamäki, Kari; Clemmensen, Peter; De Backer, Ole; Ravkilde, Jan; et al.
Summary: Background: Patients with acute ST-segment elevation myocardial infarction (STEMI) and multivessel coronary disease have a worse prognosis compared with individuals with single-vessel disease. We aimed to study the clinical outcome of patients with STEMI treated with fractional flow reserve (FFR)-guided complete revascularisation versus treatment of the infarct-related artery only. Methods: We undertook an open-label, randomised controlled trial at two university hospitals in Denmark. Patients presenting with STEMI who had one or more clinically significant coronary stenosis in addition to the lesion in the infarct-related artery were included. After successful percutaneous coronary intervention (PCI) of the infarct-related artery, patients were randomly allocated (in a 1:1 ratio) either no further invasive treatment or complete FFR-guided revascularisation before discharge. Randomisation was done electronically via a web-based system in permuted blocks of varying size by the clinician who did the primary PCI. All patients received best medical treatment. The primary endpoint was a composite of all-cause mortality, non-fatal reinfarction, and ischaemia-driven revascularisation of lesions in non-infarct-related arteries and was assessed when the last enrolled patient had been followed up for 1 year. Analysis was on an intention-to-treat basis. This trial is registered withClinicalTrials.gov, numberNCT01960933 . Findings: From March, 2011, to February, 2014, we enrolled 627 patients to the trial; 313 were allocated no further invasive treatment after primary PCI of the infarct-related artery only and 314 were assigned complete revascularisation guided by FFR values. Median follow-up was 27 months (range 12–44 months). Events comprising the primary endpoint were recorded in 68 (22%) patients who had PCI of the infarct-related artery only and in 40 (13%) patients who had complete revascularisation (hazard ratio 0·56, 95% CI 0·38–0·83; p=0·004). Interpretation: In patients with STEMI and multivessel disease, complete revascularisation guided by FFR measurements significantly reduces the risk of future events compared with no further invasive intervention after primary PCI. This effect is driven by significantly fewer repeat revascularisations, because all-cause mortality and non-fatal reinfarction did not differ between groups. Thus, to avoid repeat revascularisation, patients can safely have all their lesions treated during the index admission. Future studies should clarify whether complete revascularisation should be done acutely during the index procedure or at later time and whether it has an effect on hard endpoints. Funding: Danish Agency for Science, Technology and Innovation and Danish Council for Strategic Research.